Preface: putting the question - C. Perrin (Law Text Culture, 1998)
Terra nullius is the principle of aviolence that inheres in every origin. And in its wake there is no law, no text, no culture, free of that violence. The origin is no accident. Terra nullius is not an historical error. Our conceptual legacy is the unsettled and unsettling history of this violence. It demands critical and creative thinking. Or else, in the name of justice, equality, freedom, identity, community, sovereignty, history and, indeed, of violence itself, we are condemned to repeat this origin again and again.